Domestic Violence: A Review of Law and Protection for Women in Indonesia - Baso Asrar Sayidin; Suhendar (Catalist Indo Publisher, 2026)
This article aims to examine the forms and dynamics of domestic violence (DV) in Indonesia, evaluate the effectiveness of legal protection mechanisms, and analyse enforcement challenges under Law No. 23 of 2004 while also clarifying the evidentiary pathway for claims involving colonial land titles following Government Regulation No. 18 of 2021. The study applies normative legal research using statute and conceptual approaches through analysis of legislation, legal doctrines, and relevant secondary data concerning patterns of violence and contemporary legal practice. The findings show that domestic violence remains a serious socio-legal issue, with approximately 58.75% of reported violence occurring within households, reflecting the persistence of gender-based harm in private spheres. Although Indonesia has established a relatively comprehensive legal framework to address violence and regulate evidentiary matters, implementation remains inconsistent due to entrenched social stigma, limited institutional coordination, procedural barriers, and insufficient awareness among victims regarding their legal rights. In addition, ambiguities in evidentiary standards and administrative practices continue to affect the recognition and resolution of colonial land title claims within both judicial and bureaucratic processes. The study concludes that strengthening cross-sector collaboration, improving legal literacy, clarifying evidentiary standards, and enhancing institutional responsiveness are necessary to ensure more effective victim protection, consistent law enforcement, and greater legal certainty in Indonesia's evolving socio-legal landscape.